The effect of statins exposure during pregnancy on congenital anomalies and spontaneous abortions: A systematic review and meta-analysis - Hirsch, Ayala; Ternovsky, Natali; Zwas, Donna R.; Rotem, Reut; Amir, Offer; Hirsh Raccah, Bruria (Frontiers in Pharmacology, 2022)
Objective: To assess the effect of statin exposure during pregnancy on congenital anomalies and spontaneous abortions. Data sources: Electronic databases were searched from inception to January 2022. Study Eligibility Criteria: Cohort studies and randomized controlled trials (RCTs) evaluate the effect of treatment with statins on congenital anomalies in general and cardiac malformations in particular. Studies evaluating spontaneous abortions were included as a secondary outcome. Study appraisal and synthesis methods: Pooled odds ratio was calculated using a random-effects model and meta-regression was utilized when applicable. Results: Twelve cohort studies and RCTs were included in the analysis. Pregnancy outcomes of 2447 women that received statins during pregnancy were compared to 897,280 pregnant women who did not. Treatment with statins was not associated with a higher risk of overall congenital anomalies (Odd Ratio =1.1, CI (0.9-1.3), p=0.33, I2=0%). Yet, cardiac malformations were more prevalent among neonates born to statins users (OR=1.4, CI (1.1-1.8), p=0.02, I2=0%). The risk was higher when exposure occurred during the first trimester. This finding was statistically significant in cohort studies, but not in RCTs. Statin treatment was also associated with a higher rate of spontaneous abortions (OR=1.5, CI (1.1-2.0), p=0.005, I2=0%). In meta-regression analysis, no significant association between lipophilic statins and the rate of congenital anomalies was found. Conclusions: Overall, treatment with statins during pregnancy was not associated with an increased risk of congenital anomalies. A slight risk elevation for cardiac malformation and spontaneous abortions was seen in cohort studies but not in RCTs.